The Educational Evaluation of Tahfizul Quran Program in Boarding School: Stake Model Perspective - Sholehuddin, M Sugeng; Muhammad Sayid, Wael Ali; Amin, Abdul Basit; Aini, Rofiqotul; Mucharomah, Miftah (Cendekia: Kependidikan dan Kemasyarakatan, 2022)
This research aims to analyze the education evaluation of the Tahfizul Quran program's planning, implementation, and evaluation using the Stake model perspective in MBS Al-Hidayah Wonopringgo Pekalongan. This study also aims to analyze the obstacles in implementing the program. This research will provide academic contributions to evaluating the Tahfizul Quran program, especially in the MBS Al-Hidayah Wonopringgo Pekalongan. This qualitative study used a field research approach. The data were collected using observation, interview, and documentation techniques. They were analyzed using the Stake model, including contingency and congruence. The results of this research were (1) the planning evaluation of the program was well prepared; (2) The implementation of program evaluation according to the stage of the Stake model: inputs (antecedent), form asatiÅ¼/asatiÅ¼ah met the criteria of the Tahfiáº“ul Quran graduate school and boarding school. In contrast, the criteria of a graduate’s Bachelor had not been fulfilled. The santri have not fully fulfilled the criteria to read the Qur'an. Aspects of the curriculum already meet the criteria of the Tahfiáº“ul Quran program but lack the allocation of study time. The process of learning (transaction) was implemented according to the plan. The result of learning outcomes reached the target of each class. (3) Evaluation of the program was conducted routinely at the end of the semester.